The politics of power in an economy in transition: Eskom and the electrification of South Africa 1980-1995 - Veck, Griffith Alan (My University, 2000)
This study traces the history of the programmes to electrify white-owned commercial farms on South Africa's borders and black households, schools and clinics in the period 1980-1995 by Eskom, South Africa's public electric utility. In particular the study investigates why Eskom undertook these programmes and their macro- and micro-economic impact on the South African economy. The history of Eskom's attempt to assume responsibility for the management of Greater Soweto' s electricity supply in the late eighties is also documented. Greater Soweto is South Africa's largest and most important black township, and is situated to the south-west of Johannesburg. The reasons for this initiative and its connection to Eskom's black household electrification programmes is exposed. The methodological approach to the study involves analysing political, economic and institutional intelligence concerning Eskom's electrification programmes gathered from primary and secondary literature sources and interviews with senior Eskom staff, and others, in qualitative, and, where appropriate, quantitative terms. The results of this analysis suggest that politics played a crucial role in Eskom's decision to undertake these electrification programmes and that Eskom was an autonomous entity and lacked adequate regulatory oversight. With respect to the macro- and micro-economic benefits (GDP growth and job creation) arising from the progranune to electrify black households between 1990 and 1995 these are shown to be very much smaller than those claimed by Eskom. The reasons for this difference are explored and explained in detail. It was also found that large scale cross-subsidisation was required to sustain both the farm and black household electrification programmes. These findings required that matters of energy policy with respect to the sustainability of the programme to electrify black households be addressed. These policy issues are dealt with under three headings, financial issues, economic efficiency and equity. Finally suggestions are made for the way forward so that the electrification of black households in South Africa may be sustained.
Thesis (Ph.D.)--University of the Witwatersrand, Commerce Faculty, 2000
Keywords: Electrification--South Africa